Perlindungan Hukum terhadap Anak Sebagai Korban Eksploitasi Seksual Komersial di Media Sosial - Putu Cyntia Rizdyanti; Agung Anak Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
Indonesian citizens as a part of the elements of the world community who have a big responsibility to protect children's rights especially in human rights, which play a major role in maintaining children's welfare in social life. However, currently the exploitation of children is a problem that often occurs on social media, every child has the right to obtain a form of protection from all criminal acts of sexual exploitation. The government plays a role in protecting all forms of children's rights and providing education about the dangers of sexual exploitation on social media. This research uses the method of writing normative law which refers to the principles, norms, rules of statutory regulations, court decisions, agreements and doctrines of the technique of collecting of data carried out by the literature, legislation which is associated with the type of normative legal research by analyzing each books to select the appropriate topic of the research that is analyzed systematically and link it with other materials. The results of the research revealed that sexual exploitation of children on social media is mentioned as a violation of what is contained in dealing with the form of protection given to a child as a victim of commercial sexual exploitation on social media. The criminal offense for child exploitation is to pay one hundred million rupiahs with five years in prison.